The Legitimization Discourse of Virtue Education Under Dictatorship and Its Reception in the Schools of Soviet Latvia from 1947 to 1982 - Fernández González, Manuel Joaquín; Ķestere, Iveta; Depaepe, Marc (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This study addresses the official legitimization discourse of Soviet virtue education and its reception in school practice in Latvia. The sources capturing the official discourse were two teacher training books (1948 and 1971) and three collections of scientific papers by Latvian academics (1962, 1964, and 1967). A random sample of 10 student characterizations (graduation reports) per year from 1947 till 1982 (N=367) was used for capturing the discourse reception in school practice. The comparison of the virtue system emerging from the 3,054 mentions to students’ virtues found in the characterizations with the official Soviet virtue system revealed many similarities and also notable differences and surprising omissions: “collectivism” held a preeminent position both in the official discourse and in school practice, and “discipline” lost relative weight in both spheres, but surprisingly, the officially important “patriotism” and “internationalism” were almost absent in the characterizations. Implications for practice and further research are discussed.